Dengan Metode Bernyanyi Dapat Meningkat Daya Ingat Pada Anak - may sarah; Husni Thamrin (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Education is a very important thing in human life. However, there are still some people who think that education is only the background of life. Where they just follow the flow of their education without remembering (even forgetting) and understanding the lessons learned. This also happened to one of the children in the Al-Jam Washliyah orphanage who needed help to improve his memory in lessons. In providing assistance through Praktkum I mini project activities, using the casework method through general or general intervention stages including: Engagement intake contract, assessment, planning, intervention, and evaluation of follow-up termination. Where this process is a problem-solving strategy given to the client, namely using the singing method which aims to improve the client's learning memory. And from this strategy the client is expected to develop the coveted and capabilities.